Home warmth and health status of COPD patients. - Osman, L; Ayres, J; Garden, C; Reglitz, K; Lyon, J; Douglas, J (2008)
BACKGROUND: Home Energy Efficiency guidelines recommend domestic indoor temperatures of 21 degrees C for at least 9 h per day in living areas. Is health status of patients with Chronic Obstructive Pulmonary Disease (COPD) associated with maintaining this level of warmth in their homes? METHODS: In a cross-sectional observational study of patients, living in their own homes, living room (LR) and bedroom (BR) temperatures were measured at 30 min intervals over 1 week using electronic dataloggers. Health status was measured with the St George's Respiratory Questionnaire (SGRQ) and EuroQol: EQ VAS. Outdoor temperatures were provided by Met Office. RESULTS: One hundred and forty eight patients consented to temperature monitoring. Patients' mean age was 69 (SD 8.5) years, 67 (45%) male, mean percentage of predicted Forced Expiratory Volume in one second (FEV(1)) 41.7 (SD 17.4). Fifty-eight (39%) were current smokers. Independent of age, lung function, smoking and outdoor temperatures, poorer respiratory health status was significantly associated (P = 0.01) with fewer days with 9 h of warmth at 21 degrees C in the LR. A sub analysis showed that patients who smoked experienced more health effects than non-smokers (P < 0.01). CONCLUSION: Maintaining the warmth guideline of 21 degrees C in living areas for at least 9 h per day was associated with better health status for COPD patients. Patients who were continuing smokers were more vulnerable to reduction in warmth.